Music computer technologies as a worth-while means of folklore studying, preserving and transmission - ALIEVA, I. G.; GORBUNOVA, I. B.; MEZENTSEVA, S. V. (Utopía y Praxis Latinoamericana, 2019)
ABSTRACT With the modern threat of extinction of samples of traditional musical culture in various regions of the world, the problem of saving folklore is becoming particularly important. The Far East is a unique ethnic region where representatives of entirely different traditional cultures live. The authors use the Far East of Russia and China as an example in their study. The researchers introduce information and music computer technologies (MCT) as the means of the problem solution. Nowadays, the musicians admit the viability of MCT as the means of musical culture research, transmission, and preserving. RESUMEN Con la amenaza moderna de extinción de muestras de la cultura musical tradicional en varias regiones del mundo, el problema de salvar el folklore se está volviendo particularmente importante. El Lejano Oriente es una región étnica única donde viven representantes de culturas tradicionales completamente diferentes. Los autores utilizan el Lejano Oriente de Rusia y China como ejemplo en su estudio. Los investigadores introducen tecnologías informáticas de música e información (MCT) como el medio de la solución del problema. Hoy en día, los músicos admiten la viabilidad de MCT como medio de investigación, transmisión y preservación de la cultura musical.